Neuroinflammation co‐localizes highly with tau in amnestic mild cognitive impairment. (20th December 2022) - Appleton, Johanna; Funk, Quentin; Bradbury, Kathleen; Yu, Meixiang; Faridar, Alireza; Beers, David; Appel, Stanley H; Fujita, Masahiro; Masdeu, Joseph C.; Pascual, Belen
Abstract: Background: Neuroinflammation, along with beta amyloid and tau brain deposition, is a potential diagnostic biomarker and therapeutic target in patients with Alzheimer's disease (AD). The role of inflammation at various stages of the AD process needs to be clarified. TSPO PET is useful to image brain inflammation, but some tracers have low affinity for TSPO and "second generation" tracers, with higher affinity, cannot image subjects with a low‐binder TSPO rs6971 genotype. We overcame this problem by using 11 C‐ER176, a high‐affinity tracer allowing for imaging of all participants and with a more favorable metabolite profile than other high affinity tracers (Fujita, 2017). Then, we correlated the localization of neuroinflammation tau and amyloid in a subset of the participants. Method: We imaged 15 patients with amnestic MCI (mean age 63±5, 7 women) and 15 healthy controls (HC) (8/15 women, mean age 65 ±7) using 11 C‐ER176 PET. TSPO affinity was similar (MCI/HC = 2/3 low, 8/7 mixed, 5/5 high). A full factorial analysis was performed on V T values between groups at the regional level (Hammer's atlas). Ten MCI patients had also amyloid PET ( 18 F‐florbetaben or 18 F‐florbetapir) and tau PET ( 18 F‐flortaucipir). Standard uptake value ratios (SUVRs) were calculated for both tracers using the cerebellum as reference. Regional correlations among the three tracers were determined for each patient and an average calculated. All images were corrected for partial volume effect. Result: Neuroinflammation in MCI was bilaterally increased in precuneus and lateral temporo‐ parietal cortex, and right amygdala. There was a correlation between the localization of amyloid and tau in the brain (r=0.61). However, the correlation between neuroinflammation and tau was even higher (r=0.73); neuroinflammation also co‐localized with amyloid, but not as strongly (r=0.59). Conclusion: 11 C‐ER176 PET allowed for the identification in MCI of neuroinflammation in regions known to be involved in the AD process. Importantly, all subjects with any TSPO genotype could be studied. As expected, the localization of amyloid and tau in the brain was correlated, but the co‐localization of neuroinflammation with tau was even higher than between amyloid and tau. This finding highlights the importance of neuroinflammation as a biomarker of neurodegeneration and as a therapeutic target.